The registration of the purchase and mortgage on future assets in the real estate market: present or future assets? - Villota Cerna, Marco Antonio (2023)
This article deals with the registration in the public records of the apartments to be built and the projected housing lots, because of the prohibition of article 1106 to constitute a mortgage on future assets. For this, the positions that consider that we would find ourselves in front of present goods are analyzed and the figure of the preventive annotation as a mechanism for future assets that have a pre-independence access to the registry.In this line, the advantages of the preindependence of apartments to be built and projected housing lots are studied, to preventively record the sale and mortgage in its case; and how this would constitute a form of guarantee for the buyers of these real estate units and the banks financing these acquisitions. Likewise, a study is made of the sale and purchase of future assets, of financing and guarantees in real estate projects; and how the figure of pre-independence could contribute to boost the real estate market. Finally, the conclusions and proposals of this work are expressed.